Sedation as a technique to aid in the supportive examination for children with special needs - Primarti, Risti Saptarini; Pertiwi, Arlette Suzy Puspa (Padjadjaran Journal of Dentistry, 2007)
Undergoing medical procedures often extremely distress people, especially patients with special needs. Supportive examinations, such as radiographic and laboratory examinations, as a part of medical procedure sometimes are impossible to be done in those patients, while we demand those tests for diagnostic and treatment reasons. A variety of techniques are available to the dental and medical professional to aid in the management of these patients regarding medical procedures, one of them is sedation. By eliminating patientâs fear and anxiety throughout sedation, all medical procedure including taking a supportive examination may be successfully completed. This paper will report the role of sedation as a technique to aid in the supportive examination for special needs child (Downâs syndrome) in Hasan Sadikin General Hospital, Bandung, West Java Indonesia.